Atlas of Ultrasound Guided Musculoskeletal Injections - Spinner, David A.; Kirschner, Jonathan S.; Herrera, Joseph E.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
The use of ultrasound guidance to perform diagnostic and therapeutic injections is growing at a rapid rate, as is the evidence to support its use. Even with the increased popularity of ultrasound, there remains a lack of formal training or a standard reference book. Atlas of Ultrasound Guided Musculoskeletal Injections fills this void in the literature and will be useful to physiatrists, orthopedists, rheumatologists, pain medicine and sports medicine specialists alike. Broken down by anatomic structure and heavily illustrated, this book is both comprehensive and instructive. The Editors and their contributors break down the basics (both the fundamentals of ultrasound to needle visibility and the role of injections) and explore ultrasound-guided injection for structures in the shoulder, elbow, wrist and hand, hip and groin, knee, ankle and foot, and spine. Using a clear, heavily illustrated format, this book describes the relevant clinical scenarios and indications for injection, the evidence to support ultrasound use, relevant local anatomy, injection methods, and pearls and safety considerations. It will be a valuable reference for trainees and experienced clinicians alike, for experienced sonographers or those just starting out.
Introduction -- Shoulder -- Elbow -- Wrist and Hand -- Hip and Groin -- Knee -- Foot and Ankle -- Trigger Point -- Neuromuscular/Chemodenervation -- Spine.
Keywords: Medicine; Diagnosis, Ultrasonic; Orthopedics; Rehabilitation; Medicine & Public Health; Rehabilitation Medicine; Ultrasound; Orthopedics